It Takes Heart: The Experiences and Working Conditions of Caring Educators - Ismael, Julia; Lazzaro, Althea Eannace; Ishihara, Brianna (Radical Teacher, 2021)
At the heart of the education work that we do at our community college is a crisis that is shared, we suspect, in the majority of education settings. This is a “crisis of care” (Arruzza, Bhattacharya, Fraser 68) that emerges from the squeeze between our students’ deep and justifiable need for a caring environment in which to learn, and our desires and struggles as education workers to fulfill that need while keeping our bodies and souls together. Research on culturally responsive teaching and feminist education have demonstrated the greater ability of students to flourish when they are cared for in the classroom (Gay 48; Nodding 20, 176). But care for students, while it can be deeply satisfying for the educator, takes considerable work and skill, and providing care for a wage (especially not a livable one, especially if you are a woman of color in a predominantly white institution, especially if you are working an unwaged double-shift) can lead to burnout (Russell Hochschild 89-90; England 391-392). In the neoliberal, scarcity-based institutional contexts in which many of us work, this crisis sets the well-being of our students against the well-being of us as educators. At our college, the stories of our students’ struggles and triumphs compete in our mouths with our own stories of financial distress, long hours, and emotional exhaustion. How then, as education workers who love our students, but also love ourselves, do we do justice to each of these needs? Through a series of 3 recorded talking circles with 20 of our colleagues, we sought to answer that question by building solidarity, knowledge, and mutual aid. This paper will present the scholarship of care from education, feminism, and critical race theory, alongside the words of our colleagues to build a more complete picture of care work, emotional labor, and burnout for education workers at our community college. The paper will end with some of the ways that we are beginning to build webs of care to sustain us in our work, while we demand better conditions for ourselves and our students.